Learning Gaps and Family Experience, Nurse‐Facilitated Home Parenteral Nutrition Simulation‐Based Discharge Training: Proof‐of‐Concept Study. (7th October 2019) - Raphael, Bram P.; Takvorian‐Bené, Melissa; Gallotto, Mary; Tascione, Christina; McClelland, Jennifer; Rosa, Carolyn; Dinan, Jessica; O'Connell, Brianna; Weinstock, Peter
Abstract: Background: Home parenteral nutrition (HPN) is a life‐sustaining therapy for children and adults suffering with severe digestive diseases, yet complications are commonplace, and predischarge trainings are variable. High‐fidelity simulation training provides participants with an immersive experience using realistic equipment, supplies, and scenarios. Simulation training is rapidly becoming a potential gold standard for healthcare but is currently underutilized for families and caregivers. Methods: We prospectively collected data on pediatric patients managed at a single HPN program from September 1, 2016, to September 30, 2018. Participants in a pilot simulation‐based training program (orientation, high‐fidelity mannequin, realistic homelike space, standardized clinical scenarios, and structured debriefing) were compared with historical controls. We excluded patients with short‐term HPN use and strictly palliative goals of care. Results: Nineteen (90%) families participated in the pilot initiative with a median (interquartile range) age of 0.9 (3.7) years and diagnosis of short‐bowel syndrome in 14 (74%). During teaching scenarios, learning gaps were identified for aseptic needleless changes (53%), HPN equipment setup (84%) with specific difficulty adding multivitamin (32%), and dressing changes (63%). Thirty‐day readmission rates in simulation‐based training group vs historical cases were 42% vs 63% ( P = not significant). There was no difference in length of stay between groups. All (100%) simulation‐based training group participants would recommend this learning experience to others. Conclusion: HPN discharge training is a novel use for high‐fidelity simulation to address family/caregiver satisfaction and to identify learning gaps. Further studies are needed to refine predischarge training materials and examine the impact on postdischarge outcomes.